Improvement of physicochemical, mechanical, thermal and surface properties of anchovy by-product protein films by addition of transglutaminase, and the correlation between secondary structure and mechanical properties - Yilmaz, Kubra; Turhan, Sadettin; Sarıcaoğlu, Furkan Türker; Tural, Serpil (Elsevier, 2020)
In this study, improvement of some properties of anchovy by-product protein (ABP-P) films by addition of transglutaminase (TGase), and the correlation between secondary structural results and mechanical properties were investigated. The solubility and water vapor permeability of films improved by the TGase treatment at low concentrations. The highest tensile strength value was obtained in films containing 5 % TGase, and the elongation at break values decreased with the TGase concentration increasing. Glass transition temperature (T-g) of films decreased depending on TGase concentration and the lowest Tg was observed from 5 % TGase treated film. Fourier transform infrared spectra of films displayed similar backbone structures with different band intensities. The secondary structure of films from Amide-I band was significantly affected by TGase addition and the results were well correlated with mechanical properties. TGase addition modified the film surface structure and 3 % concentration caused the lowest surface roughness. These results revealed that mechanical, barrier and surface properties of ABP-P films could be modified with 3 % TGase treatment.
Keywords: Transglutaminase; Anchovy by-product protein; Edible film; Mechanical properties; Thermal properties; Surface properties